Error Analysis in using Personal Pronoun Mastery At the first semester of English Department - Syamsiah Depalina Siregar (Linguistik : Jurnal Bahasa dan Sastra, 2016)
English Department students need to be aware not only of their present and of future, but also the difficulties and problems they possess concerning the knowledge of general English. Especially in using the one of part of speech, it is the foundation in mastering English. It called with pronoun. The aim of the study was to collect and analyze students’ errors as markers that would point to the areas of pronoun where additional teaching and instruction is needed in order to be able to participate in the course of grammar itself. The study was carried out in 2015 at the Faculty of teacher and training, English Department in UMTS included 38 first-year students. It relies on data obtained from grammar-based placement test and from conversations with the students. Although an intermediate level of general English is necessary for participating in the course of grammar, the results show that there are areas of language that present problems to the students and need to be particularly emphasized and practiced. Students’ errors and comments on their problems may serve as useful diagnostic markers. Using these data, along with information obtained in direct communication with the students, the lecturer may develop a plan, which would help broaden the knowledge and enable the students to become more confident in professional communication in English. It is very important and useful to take advantage of the agriculture context because it presents a source of great motivation for the students.